Video-Mediated Role Play and Simulation: Enhancing Arabic Communicative Skills in Tahfiz Boarding Schools - Ahmad Farhan Rif'an Najib; Jalaluddin Jalaluddin; Zulkifli Ismail Ginting; Wildan Rosyidi; Zaki Abdul Muhaimin; Nhadzer Hassan Alvarez (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to examine the effect of the Role Play and Simulation model assisted by interactive video media on improving the listening and speaking skills of tenth-grade students at SahabatQu Tahfīdz Islamic Boarding School Yogyakarta. The study is motivated by the dominance of one-way, translation-oriented Arabic instruction, which limits the development of students’ communicative oral skills. This creates a gap between linguistic knowledge and real language use, particularly in a Tahfīdz environment that emphasizes understanding the Qur'an. This research employs a quantitative approach with a pre-experimental one-group pre-test and post-test design. The sample consists of 56 students selected through total sampling. Data were collected through listening and speaking tests administered before and after treatment and analyzed using the Shapiro-Wilk test, paired sample t-test, N-Gain, and Cohen’s d. The results show a significant improvement (Sig. 0.000 < 0.05) with a mean increase of 16 points. The N-Gain (0.51) is moderate, and the effect size (2.364) is very large, indicating strong effectiveness. This model offers an innovative approach to teaching Arabic.